Pulsed electrochemistry: A pathway to enhanced electrocatalysis and sustainable electrosynthesis - Chen Wei; He Yuanqing; Zou Yuqin; Wang Shuangyin (National Science Open, 2024)
This review delves into pulsed electrochemistry, a new technique that is becoming an essential tool in the field of electrocatalysis and electrosynthesis. Unlike traditional potentiostatic methods, pulsed electrochemical approaches provide dynamic control over catalytic reactions, leading to better selectivity, efficiency, and stability across a range of applications. We examine the underlying theory of pulsed electrocatalysis and explore how waveform characteristics, potential, and pulse time affect catalytic processes. The review pays special attention to its application in key areas such as organic electrosynthesis, CO2 reduction reactions, and water splitting, explaining how pulsed techniques improve reaction conditions to boost yields and selectivity. Meanwhile, we focus on the technique’s impact on catalyst surface modulation, managing local interface environments, and addressing issues like catalyst deactivation and mass transfer limitations. Ultimately, this review highlights the transformative potential of pulsed electrochemistry in driving various electrocatalysis and electrosynthesis applications and sets the stage for future exploration and optimization of these electrochemistry systems.